Prescription drug dependence with and without concurrent illicit drug use: a multicenter cross-sectional survey among an addiction treatment seeking population - Nawaz, Asma; Nielsen, Suzanne; Mehmood, Tahir; Abdullah, Abdullah; Ahmed, Ali; Ullah, Waseem; Khan, Ahmad (Frontiers in Psychiatry, 2023)
Background Dependence on prescription drugs and illicit drugs imposes a global health and social burden. Despite accumulating evidence of prescription drugs and illicit drugs dependence, none of the systematized studies has explored the magnitude of this problem in Pakistan. The aim is to investigate the extent and associated factors of prescription drug dependence (PDD), as opposed to concomitant prescription drug dependence and illicit drug use (PIDU), within a sample of individuals seeking addiction treatment. Methods The cross sectional study was conducted on the sample recruited from three drug treatment centers in Pakistan. Face-to-face interviews were conducted with participants who met ICD-10 criteria for prescription drug dependence. Several aspects like substance use histories, negative health outcomes, patient attitude, pharmacy and physician practices also collected to predict the determinants of (PDD). Binomial logistic regression models examined the factors associated with PDD and PIDU. Results Of the 537 treatment seeking individuals interviewed at baseline, close to one third (178, 33.3%) met criteria for dependence on prescription drugs. The majority of the participants were male (93.3%), average age of 31 years, having urban residence (67.4%). Among participants who met criteria for dependence on prescription drugs, (71.9%) reported benzodiazepines as the most frequently used drug, followed by narcotic analgesics (56.8%), cannabis/marijuana (45.5%), and heroin (41.5%). The patients reported alprazolam, buprenorphine, nalbuphine, and pentazocin use as alternatives to illicit drugs. PDD was significantly negatively associated with injectable route (OR=.281, 95% CI, .079-.993) and psychotic symptoms (OR=.315, 95% CI, .100, .986). This implies that PDD is less likely to be associated with an injectable route and psychotic symptoms in contrast to PIDU. Pain, depression and sleep disorder were primary reasons for PDD. PDD was associated with the attitude that prescription drugs are safer than illicit drugs (OR=4.057, 95%CI, 1.254-13.122) and PDD was associated with being on professional terms (i.e. having an established relationship) with pharmaceutical drugs retailers for acquisition of prescription drugs. Discussion and Conclusion The study found benzodiazepine and opioid dependence in sub sample of addiction treatment seekers. The results have implications for drug policy and intervention strategies for preventing and treating drug use disorders.